Directing WO3 crystal growth towards artificial photosynthesis favorable {002} plane via aluminum incorporation in the lattice for enhanced water splitting - Kalanur, Shankara S.; Seo, Hyungtak (Journal of Alloys and Compounds, 2021)
The {002} oriented WO3 is known to exhibit superior photoelectrochemical (PEC) water splitting O2 production compared to other facets and is generally produced via facet oriented synthesis schemes. Such schemes generally decrease surface charge transfer properties but do not alter/change the bulk charge transport characteristics. In this work, Al doping strategy is proposed to fabricate {002} facet orientated WO3 crystals with improved bulk electrical properties. Importantly, the incorporation of Al into WO3 lattice was found to decrease the resistance for bulk charge transport as well as the resistance for charge transfer between the interface of electrode and electrolyte. The optimized at% of Al-doped WO3 exhibited enhanced PEC and incident photon to current efficiencies compared to bare WO3. The proposed strategy indicates that doping with suitable material using proper synthetic scheme could be an efficient and alternate route to obtain WO3 nanocrystals with desired crystal orientation, optical and bulk electrical properties.
Keywords: Al doped; Al-doping; Alternate routes; Aluminum incorporation; Charge transfer properties; Incident photon-to-current efficiencies; Photoelectrochemicals; Water splitting; Al doping; Band structure; Carrier density; Crystal facet; Tungsten oxide